Chromatin regulation by Histone H4 acetylation at Lysine 16 during cell death and differentiation in the myeloid compartment. Issue 10 (29th March 2019) - Urdinguio, Rocio G; Lopez, Virginia; Bayón, Gustavo F; Diaz de la Guardia, Rafael; Sierra, Marta I; García-Toraño, Estela; Perez, Raúl F; García, María G; Carella, Antonella; Pruneda, Patricia C; Prieto, Cristina; Dmitrijeva, Marija; et al.
Abstract: Histone H4 acetylation at Lysine 16 (H4K16ac) is a key epigenetic mark involved in gene regulation, DNA repair and chromatin remodeling, and though it is known to be essential for embryonic development, its role during adult life is still poorly understood. Here we show that this lysine is massively hyperacetylated in peripheral neutrophils. Genome-wide mapping of H4K16ac in terminally differentiated blood cells, along with functional experiments, supported a role for this histone post-translational modification in the regulation of cell differentiation and apoptosis in the hematopoietic system. Furthermore, in neutrophils, H4K16ac was enriched at specific DNA repeats. These DNA regions presented an accessible chromatin conformation and were associated with the cleavage sites that generate the 50 kb DNA fragments during the first stages of programmed cell death. Our results thus suggest that H4K16ac plays a dual role in myeloid cells as it not only regulates differentiation and apoptosis, but it also exhibits a non-canonical structural role in poising chromatin for cleavage at an early stage of neutrophil cell death.